The Effect of Replacement Fish Mill with Golden Snail Flour in Rations on Commercial Carcasses of Male Bali Ducks - M. S., Resla; Puger, A. W.; Nuriyasa, I M. (Jurnal Peternakan Tropika, 2019)
The study aims to determine the effect of replacement fish mill with golden snail flour in rations on commercial carcasses of male bali ducks 10 weeks aged. The research design used was Randomized Block Design (RBD) with five treatments and each treatment consisted of four replications. Each replication consisted of one duck. The treatment is the R0 treatment as a control (using 15% fish mill in rations without golden snail flour), while R1, R2, R3 and R4 contain gold snail flour 25%, 50%, 75% and 100% instead of fish mill. Variables observed that the final weight, percentage of carcasses and the percentage of commercial carcasses. The results showed that the replacement of fish mill with golden snail flour in rations on final weight, percentage of carcasses and the percentage of commercial carcasses on male bali ducks by 25%, 50%, 75% and 100% are not significantly different (P>0.05) than R0. Based on the results of the study it can be concluded that the use of golden snail flour in the ration can replace the overall use of fish mill and does not affect the commercial carcass of male bali aged 10 weeks.   Keywords : Commercial Carcasses Duck, Fish Mill and Golden Snail  Flour.